The diverse virulence potential of atypical enteropathogenic Escherichia coli isolated from diarrhea: the emergence of a hybrid pathotype? - Santos, Ana C. M.; Silva, Roberta S.; Vieira, Mônica A. M.; Niero, Cristina V.; Ribeiro, Matheus S. F.; Guth, Beatriz E. C.; Gomes, Tânia A. T.; Silva, Rosa M. (Frontiers in Microbiology, 2025)
Despite being in the era of advanced technology, the world still suffers from old infectious diseases, both intestinal and extraintestinal, where Escherichia coli plays a major role as the etiological agent. Atypical enteropathogenic E. coli (aEPEC) is one of six intestinal pathogenic E. coli pathotypes and one of the major agents causing diarrhea in low- and middle-income countries like Brazil. In this work, we have investigated to what extent a collection of aEPEC isolated from the intestinal tract of children has incorporated virulence traits involved in the development of extraintestinal infections. The phylogenetic origin and the presence of extraintestinal pathogenic E. coli (ExPEC) -related Pathogenicity Islands (PAIs) were evaluated by PCR for a collection of 111 aEPEC isolated from stool. Additionally, they were screened by PCR for the presence of specific ExPEC virulence factors. Phenotypically evaluated for bacteriocin and hemolysin production and assessed for serum resistance. Finally, four strains were sequenced and had their genome characterized. Most of the strains originated from phylogroup B1 (48.6%) and A (36.3%), followed by groups B2 (13.5%) and E (8.1%). About half of the aEPEC strains presented markers for pathogenicity islands originally described in uropathogenic E. coli (UPEC), PAI IV536 being the most prevalent. Many aEPEC strains presented the virulence genetic markers that are the hallmark of ExPEC. Besides, many strains produced bacteriocins and hemolysins and survived in human serum. Five strains fulfilled the molecular criteria to be classified as ExPEC and one as UPEC, highlighting the existence of hybrid genotypes among aEPEC strains. Three non-phylogenetic-related hybrid strains were chosen for further experiments. These strains were lethal in the Galleria mellonella model for ExPEC virulence, and the comparative analysis of their genomes revealed they belong to different EPEC/ EHEC global clonal groups. Overall, this study reports the presence of many attributes of virulence of ExPEC in a comprehensive collection of aEPEC strains. The data presented here indicate the existence of genotypic hybrid aEPEC/ExPEC and aEPEC/UPEC pathogens, suggesting that they can express both intestinal and extraintestinal virulence determinants in humans. Therefore, the consequences of their colonization and infection are more concerning and potentially life-threatening.